Framing Analysis of the News of King Charles after the Death of Queen Elizabeth in French Media Le Figaro - Saidy, Humaidy Nur; Latjuba, Ade Yolanda; Annisa, Annisa (Allure Journal, 2026)
This study investigates how Le Figaro, a prominent French media outlet, framed King Charles III in the aftermath of Queen Elizabeth II's death. While numerous studies have examined the British monarchy's representation in Anglophone media, there is a scarcity of research exploring how republican media in non-English speaking contexts construct royal narratives during pivotal power transitions. Adopting a qualitative approach based on the framing analysis model by Zhongdang Pan and Gerald M. Kosicki, this research analyzes two key articles published on September 12 and 19, 2022. The analysis applies four structural dimensions: syntactic, script, thematic, and rhetorical. The results show that Le Figaro employed a hierarchical syntactic structure to emphasize King Charles III's evolution from a figure previously regarded with lesser favor to a potential leader capable of steering the monarchy forward. The script structure selectively prioritized emotional resonance and societal implications, using 5W+1H elements while downplaying geographical specifics. The thematic analysis uncovered a narrative of transformation, blending past critiques of Charles with a growing public acceptance, while the rhetorical strategies served to humanize him through evocative language and metaphors. Theoretically, this study contributes to cross-cultural media studies by demonstrating how a conservative republican media outlet negotiates the tension between institutional tradition and modern expectations. These findings highlight the unique role of ideological orientation in shaping the perception of a foreign monarch.